The influence of the bonding length on the failure mechanism of the interface between the TRC permanent formwork and cast-in-place concrete. (February 2021) - Li, Shi-chang; Yin, Shi-ping
Abstract: TRC permanent formwork is made of a new type of cement-based material and has wide application prospects in formwork engineering. To promote the large-scale development of TRC permanent formwork and make it widely used in engineering practice, based on the single-lap shear test, this paper analyses the bonding properties between the TRC permanent formwork and cast-in-place concrete at different lengths in terms of the failure mode, load-slip curve, etc., and further elaborates on the fracture mechanics theory. The research shows that when the length of the formwork small, the failure mode of the specimen measured by the single-lap shear test mainly occurs at the textile-matrix interface in the TRC permanent formwork; when the length of the TRC formwork large, the failure mode begins to change to textile fracture. The effective bonding length of the TRC permanent formwork and the cast-in-place concrete is approximately 150 mm. When the TRC formwork length is less than 150 mm, the interface bonding force increases continuously with increasing TRC formwork length. The load-slip is mainly divided into two curves with typical characteristics. The first type of curve has a clear load softening stage, and the whole curve of the second type has a stage where the slip increment is small and the load drops sharply. Finally, the interface fracture energy can better characterize the interfacial bonding properties between TRC permanent formwork and cast-in-place concrete.